Genome sequencing of Malaysian Newcastle disease viruses using next generation sequencing - Satharasinghe, Dilan Amila; Tan, Sheau Wei; Yeap, Swee Keong; Munir, Muhammad; Ideris, Aini; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Molecular detection and characterization of NDV focuses primarily on partial sequencing of the Fusion (F) gene. Complete genome sequencing by using Sanger sequencing protocols need large quantities of starting materials and high resource demanding methods such as cloning to a vectors prior to the sequence acquisition. In this study, we described the application of a simple, robust and less resource demanding methodology for whole genome sequencing of NDV by using Next Generation Sequencing (NGS) technology. This protocol was able to generate accurate consensus-level full genome sequences for 5 virulent NDVs obtained from outbreaks during 2004 to 2013. The developed method works successfully for a limited quantity of starting material and has a potential to generate the consensus level sequences within a regular high-throughput diagnostic environment. In addition, the described protocol supports parallel sequencing of 94 samples in a single sequencing run which eventually reduce considerable amount of sequencing cost per sample. Phylogenetic analysis and Pair wise Sequencing Comparison (PASC) of both partial F gene and complete genome sequences confirmed the isolates clustered with genotype VIIa or lineage 5a.